(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
There are many ceramics findings in archeological sites in the west coast of Sabah, including Sungai Padang, Papar, Tuaran, Pulau Eno, Pulau Mengalum, Pulau Rusukan Besar and Sungai Likas. The results of this study found that most of these ceramics came from different countries and time periods, such as Chinese ceramics from various dynasties, and ceramics from Southeast Asia such as Vietnam, Thailand and Cambodia. In addition, ceramics from Europe were also found. The time periods of these ceramics are the Sung Dynasty (10th-13th century AD), Yuan Dynasty (13th-14th century AD), Ming Dynasty (14th-17th century AD), Ch’ing Dynasty (17th-20th century AD), Europe (19th-20th century AD), Thailand (13th-15th century AD) and Vietnam (14th-15th century AD). These findings indicate that in the past, the west coast of Sabah was an important trading or stopover area for merchant ships due to the large number of ceramics findings from various countries and different periods. Keywords: Ceramics, trade, Southeast Asia, Sabah